2020
DOI: 10.3390/fluids5040224
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Effects of Twin-Fluid Atomization on the Suspension Plasma Spraying Process

Abstract: Suspension plasma spraying (SPS) is an effective technique to enhance the quality of the thermal barrier, wear-resistant, corrosion-resistant, and superhydrophobic coatings. To create the suspension in the SPS technique, nano and sub-micron solid particles are added to a base liquid (typically water or ethanol). Subsequently, by using either a mechanical injection system with a plain orifice or a twin-fluid atomizer (e.g., air-blast or effervescent), the suspension is injected into the high-velocity high-tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
(141 reference statements)
0
4
0
Order By: Relevance
“…When travelling the hot plasma core, ligaments and drops undergo catastrophic fragmentation at high Weber numbers (𝑊 𝑒 > 100) resulting into droplets ( tens of µm in diameter) due to Kelvin-Helmholtz and Rayleigh-Taylor fluid instabilities (46,49,50). Figure 5A displays that the liquid column, injected with a speed of about 30 m.s -1 , is actually fragmented at the neck of instabilities growing from its surface due to shearing stress.…”
Section: Plasma Liquid Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…When travelling the hot plasma core, ligaments and drops undergo catastrophic fragmentation at high Weber numbers (𝑊 𝑒 > 100) resulting into droplets ( tens of µm in diameter) due to Kelvin-Helmholtz and Rayleigh-Taylor fluid instabilities (46,49,50). Figure 5A displays that the liquid column, injected with a speed of about 30 m.s -1 , is actually fragmented at the neck of instabilities growing from its surface due to shearing stress.…”
Section: Plasma Liquid Interactionsmentioning
confidence: 99%
“…Jaddidi et al [46,47] exhaustively reviewed heat transfer in the SPS process and also highlighted the classification of breakup phenomena of liquid columns for primary fragmentation and of drops for secondary fragmentation according to the plasma gas Weber number (W e = ρ G U 2 G D/σ), the momentum flux ratio q = ρ L U 2 L /ρ G U 2 G and the Ohnesorge number of drops Oh = µ L / √ ρ L d L σ L where (ρ, U) G and (ρ, U) L are respectively, the (density, relative velocity) of the plasma gas and the liquid phase, σ L is the surface tension, µ L the dynamic viscosity of the liquid phase, D is the diameter of liquid column and d L is the diameter of the drop. According to the considerations in the previous section relating to specific enthalpy and plasma speed, mechanical fragmentation is expected due to W e > 100 while the liquid column momentum flux, or its dynamic pressure, remains higher that of the plasma jet (q > 1).…”
Section: Plasma Liquid Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the advancements in measurement technology within the micro and nano-domains have revealed that certain dynamic characteristics of these mechanical systems cannot be fully elucidated by classical mechanics. Consequently, the impact of quantum mechanics on microelectromechanical systems (MEMS) is becoming increasingly prominent, and its mode of action has garnered widespread attention in recent years [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%